FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nofi Wulandari, (2013)
This study aims to examine the factors that affect the bond rating companies listed on the Indonesia Stock Exchange. The population in this study had a number of 125 companies listed and the ranking of bonds. Pefindo period of 2012. Data obtained from the 2011 financial statements have been published. Obtained total sample of 31 companies which belong to the category of non financial companies. The analysis technique used is multiple linear regression and hypothesis testing using t-statistics and F-statistics with a confidence level of 5%. The results showed that the factors positively influence profitability and debt policies negatively affect bond ratings. While the liquidity factor positive effect on bond ratings. We advise to investors in the Indonesia Stock Exchange in order to observe the other factors that affect bond ratings in making their investment decisions.